Computer medium of estimation of aviation aggregates reliability characteristics - Приставка, А. Ф.; Мозговая, И. В.; Миначева, A. B. (Proceedings of National Aviation University (archive), 2000)
Proposed is a diagram of estimation of aviation aggregates reliability characteristics. Considered is the solution of the problems of identification, updating, approximation and distribution of their combinations